2011
DOI: 10.1186/1756-0500-4-343
|View full text |Cite
|
Sign up to set email alerts
|

Birth defects in newborns and stillborns: an example of the Brazilian reality

Abstract: BackgroundThis study constitutes a clinical and genetic study of all newborn and stillborn infants with birth defects seen in a period of one year in a medical school hospital located in Brazil. The aims of this study were to estimate the incidence, causes and consequences of the defects.MethodsFor all infants we carried out physical assessment, photographic records, analysis of medical records and collection of additional information with the family, besides the karyotypic analysis or molecular tests in indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
9
0
2
Order By: Relevance
“…Although the incidence of BDs around the world is variable, most studies report 3-5% in different populations (Oliveira et al, 2011). The incidence in this study (3.2%) corroborates previously described data despite the differences in diagnostic levels, sample sizes, and methodologies of other studies performed both in Brazil (1.4-5%) and other countries (Oliveira et al, 2011;Gill et al, 2012;Naim et al, 2013). The incidence of BDs was slightly higher in males than in females as has previously been reported (Asindi et al, 1997).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although the incidence of BDs around the world is variable, most studies report 3-5% in different populations (Oliveira et al, 2011). The incidence in this study (3.2%) corroborates previously described data despite the differences in diagnostic levels, sample sizes, and methodologies of other studies performed both in Brazil (1.4-5%) and other countries (Oliveira et al, 2011;Gill et al, 2012;Naim et al, 2013). The incidence of BDs was slightly higher in males than in females as has previously been reported (Asindi et al, 1997).…”
Section: Discussionsupporting
confidence: 89%
“…They contribute to 50% of neonatal deaths, besides being a leading cause of infant mortality and lifelong disabilities (Gill et al, 2012;Arioglu Aydin et al, 2015). About eight million babies worldwide are born each year with significant BDs (Reece, 2012); the overall incidence is approximately 3-5% (Oliveira et al, 2011;Gill et al, 2012). Although there are well-established risk factors, the causes of most BDs remain unknown (Miller et al, 2011;Kong et al, 2012;Wiener-Megnazi et al, 2012;Ooki, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Birth defects are defined as structural, functional, behavioral, and metabolic defects that develop during the organogenesis period and present at birth or detected later in life [ 2 ]. Birth defects (BDs) can be caused by genetic, chromosomal, environmental, and multifactoral effects, as well as micronutrient deficiencies or unknown etiological agents [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 Another study that was done in Saudi Arabia showed that the CNS anomalies are the most occurring anomaly followed by musculoskeletal and then renal system anomalies. 14 One study that was done in Brazil showed that the congenital anomalies are more prevalent in male as compared to female (59% male newborn and 41% in female newborn). 15 Fetal wellbeing monitoring is necessary to assess the status of fetus.…”
Section: Discussionmentioning
confidence: 99%